Feasibility of Simple Practical Project Tools Based on Local Wisdom as a Strategy to Improve Students' Science Process Skills - Nurul Aulia Rahman; St. Hayatun Nur Abu; Ilham SW Mauraji (Jurusan Pendidikan Kimia Universitas Halu Oleo, 2025)
This research aims to develop learning tools in the form of teaching modules , Student Worksheets (LKPD), observation sheets for process skills. Project-Based Learning- based science with the integration of simple practicums based on local wisdom of North Maluku to improve students' science process skills. The method used is development research with the 4D model (Define, Design, Develop, Disseminate), up to the develop stage . The define stage includes needs analysis, content analysis, and material analysis, indicating the need for contextual learning tools based on local wisdom. The design stage produces an initial draft of the teaching module and student worksheet containing contextual material. These tools are designed in line with the learning outcomes of the Independent Curriculum and indicators of science process skills. The design results will be validated at the develop stage before being widely tested. The validation results show that the teaching module and observation sheet for science process skills are in the valid category, while the student worksheet is in the very valid category.